Some issues of the legislation regulating the energy sector in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
In this article the author examines the history and development of the legislation governing the energy sector in the Republic of Kazakhstan. The need for public provision of legal mechanism for the implementation of activities on the use of renewable and alternative sources of energy is aimed at the rational use of natural resources, it is attractive from the economic side, and is necessary for energy security as a pillar of the ecological security of the state.Key words: law, environment, energy, the environment, the state.